Candidiasis in pediatric patients with cancer interned in a university hospital - Parahym,Ana Maria Rabelo De Carvalho (2009)
Fungi are common causes of infection in immunocompromised patients. Candida species are frequently involved in these cases. In order to investigate candidiasis in pediatric patients with cancer, clinical samples were collected from one hundred and twenty two patients interned in the Oswaldo Cruz University Hospital in Recife, Brazil. Yeasts were isolated from thirty-four clinical samples. The species isolated were: Candida albicans (fourteen isolates), C. parapsilosis (nine isolates), C. guilliermondii (two isolates) and C. tropicalis (two isolates). We found that candidemia was most frequent in patients with malignant hematology and that C. parapsilosis infections caused the highest mortality.